How can people’s spatial behaviour be used to dynamically lay out content on multi-user, interactive screens, and how does this dynamic layout affect people’s spatial behaviour? - Burnett, James R (2023)
This thesis aims to explore the influencing factors of layout and presentation changes of large interactive and adaptive displays in multi-user interactions and social organisation. While significant bodies of work have considered the interactivity of digital displays to identify phenomena of use, these have been conducted in localised isolation, and do not address the wider ecological impacts for the influences of emergent organisations of simultaneous use where a system or display may support this.